Tinjauan Hukum Perbandingan Pengakuan dan Pelaksanaan Putusan Arbitrase Asing di Indonesia dan Singapura - nur rizki, Raden achmad; Ansari, Teuku Syahrul; santoso, Imam budi; Arafat, Muhammad Rusli (Jurnal Ilmiah Wahana Pendidikan, 2023)
The era of globalization brings business development and increased dispute potential. Countries are forming multinational agreements to promote free markets and avoid disputes. Litigation in court as a dispute resolution tends to be long and expensive, so business people turn to arbitration which is faster and more efficient. The purpose of this study is to analyze the legal framework and mechanisms for recognition and enforcement of foreign arbitral awards in Indonesia and Singapore, comparing their approaches. It is expected to provide in-depth insights and recommendations to improve the effectiveness of business dispute resolution through international arbitration in cross-border business. This legal research uses the normative legal research method, which involves the analysis of products of legal behavior such as laws as normative case studies. . Such disputes often involve different legal systems, and therefore, a platform is needed that can resolve such disputes. International arbitration has become a popular alternative in business dispute resolution.